Development and initial validation of productive vocabulary tests for isiZulu, Siswati and English in South Africa. (October 2022) - Wilsenach, Carien; Schaefer, Maxine
Multilingualism in education is encouraged in South Africa, and children are expected to become bilingual and biliterate during the early primary grades. Much focus has been placed on measuring literacy in children's first language, often the medium of instruction (MOI), and English, the language typically used as MOI from fourth grade. However, vocabulary development in African contexts is underexplored, owing to the cost of existing English standardized tests, and the comparatively fewer linguistically and contextually appropriate vocabulary assessments in African languages. To address this gap, we document the development of corpus-informed contextually appropriate tests of productive vocabulary in isiZulu, Siswati, and English, which were used for a project evaluation. The initial validation phase included 412 children. Both tests were reliable and were concurrently validated with reading comprehension tests in each language, and oral language skills in English. This study contributes to our understanding of the factors that affect the variation in vocabulary knowledge in an African context, including age, grade repetition, and vocabulary in the other language. Only English vocabulary was affected by the remote rural location of the school. We recommend some modifications to the tests before they are validated further in other populations.